ANALYSIS OF EMPLOYEE JOB SATISFACTION FACTORS PT. DURABLE MEANS OF SUCCESS - Witna Febrianti Lasalewo; Rizal; Siske Anani (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This research aims to find out the job satisfaction of employees of PT.Durable Means of Success, this type of research is descriptive research witha qualitative approach the type of data used is primary data and secondarydata with data sourced from observations, interviews and documentation,informants in this study amounted to 5 people who are employees of PT.Durable Means of Success.The results showed that job satisfaction can be seen that job satisfactionhas been created well with five aspects, namely challenging work, salary ordecent wages, promotion or career level, supportive working conditions andsupportive coworkers.